Quantitative Model of Multi-Subject Quality Responsibility in General Contracting Projects Based on Sailed Fish Optimizer - Chen, Mingfei; He, Ying; Gao, Jie (Buildings (Basel), 2023)
In order to address the issue of the quantitative allocation of quality responsibility among different subjects in engineering general contracting projects, this paper proposed a quantitative model (M-ResQu) for multi-subject quality responsibility allocation based on quality behavior classification criteria. Firstly, utility theory and game theory were used to establish a behavioral choice model for construction units and general contractors, investigating the quality behavioral choice mechanisms in the general contracting mode. Secondly, the sailed fish optimizer (SFO) was used to screen potential laws across 84 practical judicial cases and obtain the type coefficients of three types of quality risk behaviors: technical defects, non-compliance management and non-standard behaviors. Thirdly, a fuzzy mathematics theory was employed to establish the M-ResQu model for multi-subject quality responsibility allocation in general contracting mode. Finally, a simulation analysis was conducted to demonstrate the applicability of the M-ResQu model, and results suggested that it can provide a valuable quantitative tool for quality dispute resolution in the general contracting mode.